Assessment of malignancy risk in patients with multiple sclerosis treated with intramuscular interferon beta-1a: retrospective evaluation using a health insurance claims database and postmarketing surveillance data - Bloomgren G; Sperling B; Cushing K; Wenten M (Dove Medical Press, 2012)
Gary Bloomgren, Bjørn Sperling, Kimberly Cushing, Madé WentenBiogen Idec Inc., Weston, MA, USABackground: Intramuscular interferon beta-1a (IFNβ-1a), a multiple sclerosis (MS) therapy that has been commercially available for over a decade, provides a unique opportunity to retrospectively assess postmarketing data for evidence of malignancy risk, compared with relatively limited data available for more recently approved therapies. Postmarketing and claims data were analyzed to determine the risk of malignancy in MS patients treated with intramuscular IFNβ-1a.Materials and methods: The cumulative reporting rates of suspected adverse drug reactions coded to malignancy in the intramuscular IFNβ-1a global safety database were compared with malignancy incidence rates in the World Health Organization GLOBOCAN database. In addition, using data from a large US claims database, the cumulative prevalence of malignancy in MS patients treated with intramuscular IFNβ-1a was compared with non-MS population controls, MS patients without intramuscular IFNβ-1a use, and untreated MS patients. Mean follow-up was approximately 3 years for all groups, ie, 3.1 years for the intramuscular IFNβ-1a group (range 0.02–6.0 years), 2.6 years for non-MS population controls (range 0–6.0 years), 2.6 years for the intramuscular IFNβ-1a nonuse group (range 0.01–6.0 years), and 2.4 years for the untreated MS group (range 0.01–6.0 years).Results: An estimated 402,250 patients received intramuscular IFNβ-1a during the postmarketing period. Cumulative reporting rates of malignancy in this population were consistent with GLOBOCAN incidence rates observed within the general population. The claims database included 12,894 MS patients who received intramuscular IFNβ-1a. No significant difference in malignancy prevalence was observed in intramuscular IFNβ-1a users compared with other groups.Conclusion: Results from this evaluation provide no evidence of an increased risk of malignancy with intramuscular IFNβ-1a use.Keywords: multiple sclerosis, malignancy, safety, intramuscular interferon beta-1a, postmarketing surveillance, claims